ANALISIS PENETAPAN HARGA JUAL PADA PEMBIAYAAN MURABAHAHBERDASARKAN PERSPEKTIF ISLAM DI BMT UGT SIDOGIRI CAPEMPAJARAKAN (STUDI KASUS BANK SYARIAH MANDIRI KC LUMAJANG) - wakil, Abdul (Finance : Journal of Accounting and Finance, 2024)
Abstract  This study aims to examine the determination of the selling price in murabahah financing from an Islamic perspective at BMT UGT Sidogiri Capem Pajarakan. The approach used is qualitative, with the main objective of gaining an in-depth understanding of the topic being studied. Data collection techniques were carried out through interviews, where the researcher went directly to the field to interview BMT staff, so that the data obtained would be more accurate and reliable. The results of the study indicate that the price determination mechanism applied at BMT UGT is through a negotiation process (bargaining), by forming an agreement between both parties without any element of coercion, while adhering to sharia principles. The selling price determination in murabahah contracts at BMT UGT Capem Ketompen-Pajarakan is based on the amount of financing submitted, with a margin provision ranging from 2% to 2.5%. Based on Islamic legal review, the determination of the selling price in murabahah financing at BMT UGT Capem Ketompen-Pajarakan is in accordance with sharia provisions, as it refers to DSN Fatwa No. 04/DSN-MUI/IV/2000 concerning murabahah financing.